Efeito da fotobiomodulação vascular sobre o perfil de macrófagos nas diferentes fases do processo de regeneração em modelo de lesão muscular aguda - Silva, Raquel Lira Ortiz da (2024)
Muscle injuries cause significant functional restriction and are more common in sedentary individuals or high-performance athletes. During the muscle injury process, satellite cells are activated, and inflammatory cells are recruited through the signaling of inflammatory mediators. This process leads to the presence of neutrophils and macrophages, which exhibit either pro-inflammatory or anti- inflammatory profiles, in the injured muscle microenvironment. However, disruption of this process may result in the formation of muscle fibrosis, leading to functional limitation and potential morphological alterations. Photobiomodulation therapy, applied locally (PBML) or vascularly (PBMV), has been shown in the literature to modulate inflammatory processes, increase vascularization, reduce myonecrosis, and enhance fiber diameter and cross- sectional area, in both preventive (pre) and/or therapeutic (post) applications. This study aimed to evaluate the effects of PBMV using low-level laser therapy (LLLT) on macrophage recruitment in M1 and M2 phenotypes (CD68+; CD206+) in an experimental model of acute muscle injury. A total of 85 male Wistar rats (12 weeks old) were divided into the following experimental groups: G1 - control (n=5); G2 - cryoinjury without treatment (n=20); G3 - no cryoinjury + PBMV (n=20); G4 - PBMV prior + injury (n=20); G5 - injury + PBMV (n=20). PBMV was applied to the tail vein/artery (780 nm, 40 mW, 80 s, and 3.2 J). Euthanasia was performed at four time points: 1, 2, 5, and 7 days after cryoinjury. The tibialis anterior muscle was collected for macrophage phenotype analysis (M1 - CD68+; M2 - CD206+) via immunohistochemistry, and data were subjected to statistical analysis. CD68+ cell immunostaining revealed a significant inflammatory infiltrate on day 1, with the highest cell count in the PBMV prior + injury group, peaking on day 2 and progressively decreasing by day 7 in irradiated groups. CD206+ cells were most abundant in the PBMV prior + injury group on day 1, peaked on day 2, and significantly reduced by day 7, especially in the PBMV post-injury group. Cellular recruitment peaked on day 2, followed by a decline or stabilization depending on the PBMV strategy. We conclude that PBMV effectively modulates macrophage recruitment, with preventive PBMV accelerating the arrival of these cells in the injured environment.